(untitled) (BrewingScience, 2000)
During the course of the EBC held at Cannes during May and June 1999 a workshop was held to discuss a number of the posters related to yeasts. The workshop was jointly run by David Ryder from Miller Brewing and Poul Sigsgaard from the Scandinavian School of Brewing. In his introduction David reminded his audience of the importance of yeasts for beer production; happy yeasts will produce beers which delight the brewers’ customers whereas unhappy yeasts will lead to problems with both flavour consistency and flavour stability. Five posters had been selected from those displayed at the Congress and their authors were asked to make a short presentation setting out the main findings of their work. In particular, they were asked to answer three questions: What is the primary discovery of your contribution? How important is this in terms of yeast? How far is the work from implementation and use? Encouraged by the chairmen (in some cases forcibly) the small but select band of participants then debated the implications of the work.